2017
DOI: 10.1021/acs.jpclett.7b01634
|View full text |Cite
|
Sign up to set email alerts
|

DFT-Assisted Polymorph Identification from Lattice Raman Fingerprinting

Abstract: A combined experimental and theoretical approach, consisting of lattice phonon Raman spectroscopy and density functional theory (DFT) calculations, is proposed as a tool for lattice dynamics characterization and polymorph phase identification. To illustrate the reliability of the method, the lattice phonon Raman spectra of two polymorphs of the molecule 2,7-dioctyloxy[1]benzothieno[3,2-b]benzothiophene are investigated. We show that DFT calculations of the lattice vibrations based on the known crystal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 40 publications
11
72
0
Order By: Relevance
“…There is no way to prevent molecules to vibrate around their equilibrium position on a crystal lattice, but rigid structures allow only tiny displacements, Δ x , and hence a low broadening of the width of the distribution of transfer integrals, Δ J , as schematically illustrated in Figure . In fact, phonon engineering is easily accessible to chemists, i.e., low‐frequency Raman modes, in the 10–150 cm −1 spectral window, must simply be measured on crystals of molecular semiconductors . The higher the frequency of the first intermolecular phonon mode is, the lower the displacement around equilibrium position is, and ultimately the narrower the distribution of transfer integrals is …”
Section: Charge Transportmentioning
confidence: 99%
“…There is no way to prevent molecules to vibrate around their equilibrium position on a crystal lattice, but rigid structures allow only tiny displacements, Δ x , and hence a low broadening of the width of the distribution of transfer integrals, Δ J , as schematically illustrated in Figure . In fact, phonon engineering is easily accessible to chemists, i.e., low‐frequency Raman modes, in the 10–150 cm −1 spectral window, must simply be measured on crystals of molecular semiconductors . The higher the frequency of the first intermolecular phonon mode is, the lower the displacement around equilibrium position is, and ultimately the narrower the distribution of transfer integrals is …”
Section: Charge Transportmentioning
confidence: 99%
“… a) Chemical structure of C 8 O‐BTBT‐OC 8 , b) parallel stacking of the aromatic cores in the bulk phase, and c) herringbone stacking motif in the in the SIP . Carbon atoms are drawn dark gray in the aromatic core and light gray in the alkyl chains, sulfur atoms are yellow, and oxygen atoms are red; hydrogen atoms have been removed for clarity.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, two spectroscopy techniques are used to characterize polymorphism in drop‐cast and spin‐coated C 8 O‐BTBT‐OC 8 thin films, whereas it is also shown that single crystals of the two known polymorphs can be grown from solution. The bulk and SIP polymorphs of C 8 O‐BTBT‐OC 8 differ greatly in their molecular packing arrangements: The bulk phase shows a slipped π–π‐stacked motif (Figure b), whereas the SIP presents a herringbone structure (Figure c) . The crystallographic data of both structures are given in Table .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations on molecular crystals using programs that enable to include the periodic boundary conditions of a studied system and a planewave basis set has proven to be very accurate. Among many features that can be calculated for the optimized crystal structures the spectroscopic (NMR, IR, or Raman) properties are commonly requested to explain the experimental results or to guide the experimental data acquisition …”
Section: Introductionmentioning
confidence: 99%